Online Gaming Addiction and Emotional Disorders Among Adolescents: A Cross-Sectional Study in a Public Junior Secondary School - Luluk Mufariha; Galuh Kumalasari; Frastiqa Fahrany; Kon Alier (Tarqabin Nusantara Group, 2026)
The rapid global expansion of online gaming has raised increasing concerns regarding gaming addiction and its psychological consequences among adolescents, particularly in low- and middle-income countries where evidence remains limited. This study aimed to examine the association between online gaming addiction and emotional disorders among adolescents attending a public junior secondary school in East Java, Indonesia. A cross-sectional study with stratified random sampling was conducted among 142 students (mean age 13.1 years; 61.3% male). Data were collected using the Internet Gaming Disorder Scale-20 (IGDS9-SF) and the Strengths and Difficulties Questionnaire (SDQ), then analysed using Spearman’s rank correlation and multivariate ordinal regression. Most respondents demonstrated moderate gaming addiction (55.6%), while 2.1% met criteria for high addiction. Emotional disorders were identified in 51.4% of participants, consisting primarily of behavioural disorders (42.5%), depression (34.3%), and anxiety (23.2%). Spearman’s analysis revealed a significant positive correlation between gaming addiction and emotional disorders (r = 0.41, p = 0.001). Multivariate analysis further showed that gaming addiction independently predicted emotional disorders after adjustment for age and sex (adjusted OR = 3.12; 95% CI: 1.68–5.79; p < 0.001). Behavioural disturbance emerged as the most prominent emotional manifestation. These findings highlight the importance of integrating school-based mental health screening and preventive interventions into adolescent health policies in Indonesia.